Data for Development Profiles Official Development Assistance for Data and Statistical Systems. - OECD. (OECD Publishing, 2021)
Sound and timely data and statistics are essential for designing better policies for better lives. When the right data are available and used by policy makers, they play a crucial role in managing crises, as revealed during the COVID-19 pandemic.